Un report dal Workshop IGAW2016 sul GNSS che fa riflettere sul futuro della geomatica - Carlucci, Renzo (GEOmedia, 2016)
Sogei, a company of the Ministry of Finance, which has about 2000 engineers with a R&D Laboratory on positioning, mapping and GNSS, on 21 and 22 January 2016 has realized a workshop mainly aimed at the discussion on the reliability of multi-constellation positioning systems, with speaker coming from the top of academy and industry that have given life to a high-level international event.